Experts in science, laypersons in politics: What psychologists for public policies? - Jorge Alvaro Chavez Bidart; Pablo Piquinela Averbug (Escuela de Psicología, Pontificia Universidad Católica de Valparaíso, 2017)
The beginning of the 21st century, in most of Latin America, is characterized by the strong presence of the state in the attempt to solve the population's problems. Public policies have been the privileged way of intervening on problems from the work of social experts, especially professionals in psychology. Studies about the practices of psychologists in public policies revealed deficiencies in training, reduction of critical analysis on intervention modalities, as well as the weakening of political dimensions on the practices reflection. Starting from the presentation of empirical studies on professional psychologist's practices in public policies, and considering the contributions of studies in science, technology and society, we will analyze how psychologists produce the role of experts and the relationships between experts and population. We are interested in recovering political reflection about practices, analyzing the ways of living the politics, the public issues and the relations between experts and population which are translated by psychologists through our professional practices.